Titanium-based composite lead material for high-energy ray protection and preparation method thereof

CN122979703APending Publication Date: 2026-10-27SHAANXI TIANRUN SHANGJIAN MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611149185.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0023]上述制备方法中,烧结温度、烧结压力和保温时间控制在上述范围内,可以使钛基体形成稳定骨架,并使金属相在钛基体层与铅层之间形成过渡连接区域。当烧结温度小于950 ℃或保温时间小于5 min时,界面连接不足;当烧结温度大于1050 ℃或保温时间大于20 min时,铅层容易发生过度流动、局部堆积或界面失稳。将烧结温度控制在950 ℃~1050℃、烧结压力控制在60 MPa~200 MPa、保温时间控制在5 min~20 min,可以提高材料的致密度、界面结合稳定性和结构稳定性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a titanium-based composite lead material for high-energy ray protection and a preparation method thereof. The titanium-based composite lead material comprises at least one titanium-based composite layer, the titanium-based composite layer comprises a titanium matrix, a metal phase and a lead phase, the metal phase is at least partially distributed between the titanium matrix and the lead phase; the volume percentage of the titanium matrix is 60 vol% to 77 vol% based on the total volume of the titanium-based composite layer, the volume percentage of the lead phase is 20 vol% to 35 vol%, and the volume percentage of the metal phase is 1 vol% to 8 vol%. The application can improve the structural stability and ray shielding performance of the titanium-based composite lead material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of radiation protection materials technology, and more specifically, to a titanium-based composite lead material for high-energy radiation protection and its preparation method. Background Technology

[0002] High-energy rays such as X-rays and gamma rays are widely used in medical radiotherapy, industrial flaw detection, nuclear industry, military and aerospace fields. In these applications, radiation protection materials need to have sufficient shielding capacity against high-energy rays, while also meeting requirements for structural load-bearing capacity, installation and construction, long-term service safety, and environmental friendliness. With the increasing demands on radiation protection materials, improving the structural stability and radiation shielding performance of composite lead materials is a pressing technical problem that needs to be solved. Summary of the Invention

[0003] This application provides a titanium-based composite lead material for high-energy radiation protection and its preparation method, which can improve the structural stability and radiation shielding performance of the titanium-based composite lead material.

[0004] In a first aspect, a titanium-based composite lead material is provided, comprising at least one titanium-based composite layer, the titanium-based composite layer comprising a titanium matrix, a lead phase and a metallic phase, wherein the metallic phase is at least partially distributed between the titanium matrix and the lead phase; based on the total volume of the titanium-based composite layer, the volume percentage of the titanium matrix satisfies 60 vol% to 77 vol%, the volume percentage of the lead phase satisfies 20 vol% to 35 vol%, and the volume percentage of the metallic phase satisfies 1 vol% to 8 vol%.

[0005] In this embodiment, the titanium matrix serves as the main framework, enhancing the material's tensile strength, impact resistance, and service stability. A titanium matrix volume percentage of 60 vol%–77 vol% ensures a relatively stable load-bearing framework; a volume percentage less than 60 vol% results in insufficient framework support; a volume percentage greater than 77 vol% leads to a corresponding decrease in lead content, potentially causing insufficient X-ray shielding efficiency. The lead phase, as a high atomic number shielding phase, with a volume percentage of 20 vol%–35 vol%, improves the material's ability to block and attenuate X-rays, and reduces localized accumulation or excessively high material density caused by excessive lead content. The metallic phase is at least partially distributed between the titanium matrix and the lead phase interface; a metallic phase content less than 1 vol% provides insufficient interface transition and bonding improvement; a metallic phase content greater than 8 vol% may weaken the continuity of the titanium matrix framework. Through the above proportions and interface distribution, the risks of interface separation and lead phase agglomeration can be reduced, improving the structural stability and X-ray shielding performance of the titanium-based composite lead material.

[0006] In one possible implementation, the metallic phase material includes copper and / or nickel.

[0007] In this embodiment, copper or nickel can serve as a transition metal phase between the titanium matrix and the lead phase, alleviating the problems of poor wettability and weak interfacial bonding between titanium and lead. Copper is chosen as the metal phase because it improves interfacial wetting and bonding, reducing the risk of localized undulations, debonding, or peeling of the lead phase. Nickel is chosen as the metal phase because it enhances the thermal stability and long-term service stability of the interfacial structure, thereby improving the structural and interfacial stability of the titanium-based composite lead material.

[0008] In one possible implementation, the volume average particle size Dv50 of the metallic phase satisfies: 1 μm to 3 μm.

[0009] In this embodiment, the metal phase particle size is greater than 3 μm, making it difficult to fully penetrate the fine gaps between titanium and lead powders, easily resulting in a lack of transition phase in local areas; the metal phase particle size is less than 1 μm, resulting in an excessively large powder specific surface area, which easily leads to agglomeration or oxidation, thus hindering dispersion. Therefore, the metal phase in the particle size range of 1 μm to 3 μm is more likely to penetrate the interparticle gaps between titanium and lead powders, thereby increasing the contact area between the metal phase and the titanium matrix and lead phase. This improves the interfacial filling capacity and powder dispersion stability of the material, enhances the coverage stability of the lead layer in the composite lead material, and thus improves the interfacial stability of the composite lead material.

[0010] In one possible implementation, the titanium matrix material comprises titanium powder, the volume average particle size Dv50 of which satisfies: 20 μm to 50 μm.

[0011] In this embodiment, when the titanium powder particle size is greater than 50 μm, the surface undulations and interparticle gaps of the titanium matrix are relatively large, which can easily lead to uneven lead layer coverage, local accumulation, or decreased interface continuity. When the titanium powder particle size is less than 20 μm, the specific surface area of ​​the titanium powder increases, making the powder prone to oxidation and agglomeration, increasing the difficulty of mixing and sintering, making it difficult to obtain a high-density composite material, and reducing shielding performance and service life. When the titanium powder particle size is controlled between 20 μm and 50 μm, the titanium powder can form a supporting framework and a relatively stable matrix support surface, and also provide a suitable bonding foundation for the metallic mesophase and lead layer. This allows the lead layer to cover the titanium matrix layer smoothly and uniformly under the action of the metallic mesophase, improving the structural stability and shielding performance of the composite lead material.

[0012] In one possible implementation, the lead phase material includes lead powder, and the volume average particle size Dv50 of the lead powder satisfies: 5 μm to 15 μm.

[0013] In this embodiment, when the lead powder particle size is greater than 15 μm, the particle size is too large, which can easily cause local accumulation, uneven thickness, or discontinuous interface contact of the lead layer after molding and sintering, resulting in local weak areas in the radiation shielding performance. When the lead powder particle size is less than 5 μm, the specific surface area of ​​the powder increases, making it prone to agglomeration, oxidation, or segregation during mixing, making it difficult to form a continuous and stable lead layer and reducing the radiation shielding effect. Controlling the lead powder particle size between 5 μm and 15 μm is beneficial for the lead powder to form a more continuous and flat lead layer during molding and sintering, and to maintain a stable bond with the titanium matrix layer through the metallic intermediate phase, thereby improving the radiation shielding performance and interface stability of the composite lead material.

[0014] In one possible implementation, the lead phase material includes lead powder, the volume average particle size Dv50 of which satisfies: 6 μm to 13 μm.

[0015] In this embodiment, the volume average particle size Dv50 of the lead powder is further controlled within 6 μm to 13 μm, which can reduce the risk of agglomeration and oxidation caused by excessively fine lead powder, while maintaining the ability of lead powder to form a continuous lead layer and improving the interfacial stability of the composite lead material.

[0016] Secondly, a method for preparing a titanium-based composite lead material for high-energy radiation protection is provided, the method comprising: Titanium powder, lead powder, and other metal materials are weighed and subjected to high-energy ball milling and ultrasonic dispersion to obtain a mixed powder. The mixed powder is then subjected to cold isostatic pressing to obtain a preform. The preform is then subjected to spark plasma sintering and cooled to obtain a titanium-based composite lead material.

[0017] In the above preparation method, the combination of high-energy ball milling and ultrasonic dispersion can reduce the agglomeration of lead powder and metal raw materials during the mixing process, making it easier for the metal raw materials to be located at the interface between titanium powder and lead powder, and forming a sufficient metal intermediate phase transition after sintering. Cold isostatic pressing can improve the density of the preform and reduce localized loose areas of powder, thus reducing localized accumulation, undulations, or interface defects in the lead layer caused by uneven density of the preform. Spark plasma sintering can complete powder densification within a short holding time, reducing the risk of excessive lead layer flow and interface separation, and minimizing the decrease in shielding performance caused by interface separation and damage to the lead layer coverage. This results in a composite lead material with high radiation shielding efficiency and good interfacial bonding stability.

[0018] In one possible implementation, the ball-to-material ratio of the high-energy ball milling process is 5:1 to 9:1, the rotation speed is 400 rpm to 800 rpm, the ball milling time is 3 h to 6 h; and / or, the frequency of the ultrasonic dispersion is 15 kHz to 50 kHz.

[0019] In the above preparation methods, when the ball-to-powder ratio is less than 5:1 or the rotation speed is less than 400 rpm, the impact and shearing effect of the grinding balls on the powder is insufficient, making it difficult for the metallic phase to be fully located at the interface between titanium powder and lead powder. After sintering, local deficiencies in the intermediate metallic phase or uneven lead layer coverage are likely to occur, reducing the X-ray shielding performance. When the ball-to-powder ratio is greater than 9:1 or the rotation speed is greater than 800 rpm, the powder is prone to cold welding and adhesion or the introduction of too many impurities, which in turn damages the smoothness of the lead layer coverage and the stability of the interface. When the ball milling time is less than 3 hours, the mixing is insufficient, and the metallic phase is difficult to be located in the titanium-lead interface region. When the ball milling time is greater than 6 hours, the powder is overly refined, which is prone to oxidation and agglomeration, which is not conducive to the formation of a stable intermediate metallic phase and lead layer coverage structure. By limiting the ball-to-powder ratio, rotation speed, and ball milling time within the above ranges, and combining them with ultrasonic dispersion treatment, the powders of each phase can be fully mixed, and the raw materials of the metallic material can be effectively located between titanium powder and lead powder. Finally, after sintering, a sufficient interfacial transition connection is formed, ensuring the shielding performance of the composite lead material against high-energy X-rays and gamma rays.

[0020] In one possible implementation, the molding pressure of the cold isostatic pressing process is 1000 MPa to 3000 MPa, and the holding time is 15 min to 40 min.

[0021] In the above preparation methods, when the molding pressure is less than 1000 MPa, the bonding force between powder particles is insufficient, resulting in low density of the preform. Loose areas of the powder are prone to forming pores or cracks during subsequent sintering, leading to a decrease in X-ray shielding performance. When the molding pressure is greater than 3000 MPa, titanium powder particles may undergo excessive plastic deformation, damaging the integrity of the titanium matrix skeleton. Simultaneously, lead powder particles may be excessively compressed, forming localized lead phase accumulation or interface undulations. When the holding time is less than 15 min, pressure transmission is insufficient, resulting in uneven density distribution within the preform. When the holding time is greater than 40 min, the density increase tends to saturate. By limiting the molding pressure and holding time within the above ranges, a dense and uniform preform can be obtained, thus fully utilizing the shielding performance of composite lead materials against high-energy X-rays and gamma rays.

[0022] In one possible implementation, the sintering temperature of the spark plasma sintering treatment is 950 ℃~1050 ℃, the sintering pressure is 60 MPa~200 MPa, and the holding time is 5 min~20 min.

[0023] In the above preparation method, controlling the sintering temperature, sintering pressure, and holding time within the specified range allows the titanium matrix to form a stable framework and enables the metallic phase to form a transitional bonding region between the titanium matrix layer and the lead layer. When the sintering temperature is less than 950 °C or the holding time is less than 5 min, the interfacial bonding is insufficient; when the sintering temperature is greater than 1050 °C or the holding time is greater than 20 min, the lead layer is prone to excessive flow, local accumulation, or interfacial instability. Controlling the sintering temperature between 950 °C and 1050 °C, the sintering pressure between 60 MPa and 200 MPa, and the holding time between 5 min and 20 min can improve the material's density, interfacial bonding stability, and structural stability. Detailed Implementation

[0024] The technical solutions of this application will be described below with reference to embodiments. It should be understood that the following embodiments are only used to explain the technical solutions of this application and are not intended to limit the scope of protection of this application. Conventional adjustments made by those skilled in the art to the source of raw materials, specific product form, component size or process parameters without departing from the technical concept of this application should all fall within the scope of protection of this application.

[0025] In this application, "lead phase" refers to a phase structure with lead as the main component and used to improve the radiation shielding efficiency of materials. "Lead powder" is the raw material form that forms the lead phase. After mixing, molding, and sintering, the lead powder forms the lead phase in the material.

[0026] In this application, "titanium-based composite lead material" or "composite lead material" refers to a composite material comprising a titanium matrix and a lead phase, with the lead phase serving as the radiation shielding phase. "Titanium matrix" refers to the phase structure in which titanium is the main component and constitutes the load-bearing skeleton of the composite material.

[0027] In this application, "vol%" refers to volume percentage. Unless otherwise stated, the volume percentages of the titanium matrix, lead phase, and metallic phase are calculated based on the total volume of the titanium-based composite layer.

[0028] "Volume average particle size Dv50" refers to the particle size corresponding to a cumulative volume fraction of 50% in the particle size distribution of powder. It can be determined using conventional laser particle size analysis, sieving, or microscopic statistical methods in this field.

[0029] In this application, "high-energy rays" includes X-rays, gamma rays, and other types of rays with strong penetrating power that require shielding. In specific embodiments of this application, X-ray and gamma-ray protection applications are used as examples for illustration.

[0030] Lead, due to its high atomic number and density, is a widely used material in traditional high-energy radiation shielding materials. Pure lead material, at a certain thickness, has a good blocking and attenuation effect on X-rays and gamma rays, and is therefore widely used in components such as protective walls, protective doors, equipment shielding covers, and mobile protective screens.

[0031] However, pure lead still has several drawbacks when used as a high-energy radiation shielding material. First, pure lead has a high density; using thicker lead layers for high-energy gamma-ray protection results in heavier shielding components, increasing the load on walls, supports, mobile devices, and equipment housings. Second, pure lead is relatively soft and has low mechanical strength; it is prone to denting, creep, or cracking after prolonged pressure or impact, and the joints can easily lead to radiation leakage risks. Third, pure lead may generate lead dust or lead fumes during processing, cutting, welding, installation, aging, and disposal, posing occupational health and environmental pollution risks. Furthermore, high-energy radiation interacting with lead may produce characteristic lead X-rays; traditional solutions typically require additional absorbing layers such as copper or aluminum, making the shielding structure more complex.

[0032] To address the shortcomings of pure lead materials, existing technologies include composites of lead with other metals, ceramics, or polymers. Titanium, with its low density, good mechanical properties, and excellent corrosion resistance, is theoretically suitable as a structural matrix for composite protective materials. However, the significant differences in physicochemical properties between titanium and lead can easily lead to problems such as insufficient interfacial bonding, delamination, debonding, lead phase agglomeration, or lead phase precipitation when directly composited. These issues can reduce the structural stability of the composite material and potentially result in insufficient localized shielding capabilities.

[0033] Therefore, this application provides a titanium-based composite lead material. This titanium-based composite lead material includes at least one titanium-based composite layer, which comprises a titanium matrix, a lead phase, and a metallic phase, with the metallic phase at least partially distributed between the titanium matrix and the lead phase. Based on the total volume of the titanium-based composite layer, the volume percentage of the titanium matrix is ​​60 vol% to 77 vol%, the volume percentage of the lead phase is 20 vol% to 35 vol%, and the volume percentage of the metallic phase is 1 vol% to 8 vol%.

[0034] For example, the volume percentage of the titanium matrix can be 60 vol%, 62 vol%, 64 vol%, 66 vol%, 68 vol%, 70 vol%, 72 vol%, 74 vol%, 76 vol%, 77 vol%, or any value within the above range. The volume percentage of the lead phase can be 20 vol%, 25 vol%, 30 vol%, 32 vol%, 35 vol%, or any value within the above range. The volume percentage of the metallic phase can be 1 vol%, 3 vol%, 5 vol%, 6 vol%, 8 vol%, or any value within the above range.

[0035] In this embodiment, the titanium matrix serves as the main framework, enhancing the material's tensile strength, impact resistance, and service stability. A titanium matrix volume percentage of 60 vol%–77 vol% ensures a relatively stable load-bearing framework; a volume percentage less than 60 vol% results in insufficient framework support; a volume percentage greater than 77 vol% leads to a corresponding decrease in lead content, potentially causing insufficient X-ray shielding efficiency. The lead phase, as a high atomic number shielding phase, with a volume percentage of 20 vol%–35 vol%, improves the material's ability to block and attenuate X-rays, and reduces localized accumulation or excessively high material density caused by excessive lead content. The metallic phase is at least partially distributed at the interface between the titanium matrix and the lead phase; a metallic phase content less than 1 vol% results in insufficient interface transition and bonding improvement; a metallic phase content greater than 8 vol% may weaken the continuity of the titanium matrix framework. Through the above proportions and interface distribution, the risks of interface separation and lead phase agglomeration can be reduced, improving the interfacial bonding stability, structural stability, and X-ray shielding performance of the titanium-based composite lead material.

[0036] It should be noted that when composite lead materials are used as shielding layers or shielding components, they do not have the function of actively eliminating radiation, but rather they block and attenuate radiation to improve the radiation shielding efficiency of composite lead materials.

[0037] In this application, "metallic phase" refers to a transitional metallic phase that is at least partially located or distributed at the interface between the titanium matrix and the lead phase, and locally may manifest as a metallic intermediate phase composed of copper or nickel. This metallic phase mainly plays a role in improving interface transition and bonding.

[0038] In one embodiment, the metallic phase material includes copper and / or nickel.

[0039] In the above embodiments, copper or nickel can serve as a transition metal phase between the titanium matrix and the lead phase, alleviating the problems of poor wettability and weak interfacial bonding between titanium and lead. Copper is used as the metal phase because it improves interfacial wetting and bonding, reducing the risk of localized undulations, debonding, or peeling of the lead phase. Nickel is used as the metal phase because it enhances the thermal stability and long-term service stability of the interfacial structure, thereby improving the structural and interfacial stability of the titanium-based composite lead material.

[0040] In one embodiment, the volume average particle size Dv50 of the metallic phase satisfies: 1 μm to 3 μm.

[0041] For example, the volume average particle size of the metallic phase can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any value within the above range.

[0042] In the above embodiments, the metal phase particles larger than 3 μm have difficulty fully penetrating the fine gaps between titanium and lead powders, easily resulting in a lack of transition phase in local areas; the metal phase particles smaller than 1 μm have an excessively large powder surface area, making them prone to agglomeration or oxidation, which is detrimental to dispersion. Therefore, the metal phase in the particle size range of 1 μm to 3 μm is more likely to enter the interparticle gaps between titanium and lead powders, thereby increasing the contact area between the metal phase and the titanium matrix and lead phase. This improves the interfacial filling capacity and powder dispersion stability of the material, enhances the coverage stability of the lead layer in the composite lead material, and thus improves the interfacial stability of the composite lead material.

[0043] In one embodiment, the titanium matrix material comprises titanium powder, and the volume average particle size Dv50 of the titanium powder satisfies: 20 μm to 50 μm.

[0044] For example, the volume average particle size of the titanium powder can be 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, or any value within the above range.

[0045] In the above embodiments, when the titanium powder particle size is greater than 50 μm, the surface undulations and interparticle gaps of the titanium matrix are relatively large, which can easily lead to uneven lead layer coverage, local accumulation, or decreased interface continuity. When the titanium powder particle size is less than 20 μm, the specific surface area of ​​the titanium powder increases, making the powder prone to oxidation and agglomeration, increasing the difficulty of mixing and sintering, making it difficult to obtain a high-density composite material, and reducing shielding performance and service life. When the titanium powder particle size is controlled between 20 μm and 50 μm, the titanium powder can form a supporting skeleton and a relatively stable matrix support surface, and also provide a suitable bonding foundation for the metallic mesophase and lead layer. This allows the lead layer to cover the titanium matrix layer smoothly and uniformly under the action of the metallic mesophase, improving the structural stability and shielding performance of the composite lead material.

[0046] In one embodiment, the lead phase material comprises lead powder, and the volume average particle size Dv50 of the lead powder satisfies: 5 μm to 15 μm.

[0047] For example, the volume average particle size of lead powder can be 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, or any value within the above range.

[0048] In the above embodiments, when the lead powder particle size is greater than 15 μm, the particle size is too large, which can easily cause local accumulation, uneven thickness, or discontinuous interface contact of the lead layer after molding and sintering, resulting in local weak areas in the radiation shielding performance. When the lead powder particle size is less than 5 μm, the specific surface area of ​​the powder increases, making it prone to agglomeration, oxidation, or segregation during mixing, making it difficult to form a continuous and stable lead layer and reducing the radiation shielding effect. Controlling the lead powder particle size between 5 μm and 15 μm is beneficial for the lead powder to form a more continuous and flat lead layer during molding and sintering, and to maintain a stable bond with the titanium matrix layer through the metallic intermediate phase, thereby improving the radiation shielding performance and interface stability of the composite lead material.

[0049] In one possible implementation, the lead phase material includes lead powder, the volume average particle size Dv50 of which satisfies: 6 μm to 13 μm.

[0050] In this embodiment, the volume average particle size Dv50 of the lead powder is further controlled within 6 μm to 13 μm, which can reduce the risk of agglomeration and oxidation caused by excessively fine lead powder, while maintaining the ability of lead powder to form a continuous lead layer and improving the interfacial stability of the composite lead material.

[0051] The preparation method of the titanium-based composite lead material for high-energy radiation protection provided in this application embodiment may include the following steps: S1: Weigh titanium powder, lead powder, and metallic raw materials, and perform high-energy ball milling and ultrasonic dispersion to obtain a mixed powder; wherein, based on the total volume of the mixed powder, the volume percentage of titanium powder is 60 vol% to 77 vol%, the volume percentage of lead powder is 20 vol% to 35 vol%, and the volume percentage of metallic raw materials is 1 vol% to 8 vol%. S2: The mixed powder is subjected to cold isostatic pressing to obtain a preform; S3: The preform is subjected to spark plasma sintering and cooled to obtain composite lead material.

[0052] In the above preparation method, the combination of high-energy ball milling and ultrasonic dispersion can reduce the agglomeration of lead powder and metal raw materials during the mixing process, making it easier for the metal raw materials to be located at the interface between titanium powder and lead powder, and forming a sufficient metal intermediate phase transition after sintering. Cold isostatic pressing can improve the density of the preform and reduce localized loose areas of powder, thus reducing localized accumulation, undulations, or interface defects in the lead layer caused by uneven density of the preform. Spark plasma sintering can complete powder densification within a short holding time, reducing the risk of excessive lead layer flow and interface separation, and minimizing the decrease in shielding performance caused by interface separation and damage to the lead layer coverage. This results in a composite lead material with high radiation shielding efficiency and good interfacial bonding stability.

[0053] In one embodiment, the ball-to-material ratio of the high-energy ball milling process is 5:1 to 9:1, the rotation speed is 400 rpm to 800 rpm, the ball milling time is 3 h to 6 h; and / or, the frequency of the ultrasonic dispersion is 15 kHz to 50 kHz.

[0054] For example, the ball-to-material ratio in the high-energy ball milling process can be 5:1, 6:1, 7:1, 8:1, 9:1, or any value within the above range. The rotational speed of the high-energy ball milling process can be 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, or any value within the above range. The ball milling time of the high-energy ball milling process can be 3 h, 4 h, 5 h, 6 h, or any value within the above range. The frequency of the ultrasonic dispersion can be 15 kHz, 20 kHz, 30 kHz, 40 kHz, 50 kHz, or any value within the above range.

[0055] In the above embodiments, when the ball-to-powder ratio is less than 5:1 or the rotation speed is less than 400 rpm, the impact and shearing effect of the grinding balls on the powder is insufficient, making it difficult for the metallic phase to be fully located at the interface between titanium powder and lead powder. After sintering, local deficiencies in the intermediate metallic phase or uneven lead layer coverage are likely to occur, reducing the X-ray shielding performance. When the ball-to-powder ratio is greater than 9:1 or the rotation speed is greater than 800 rpm, the powder is prone to cold welding and adhesion or the introduction of too many impurities, which in turn damages the smoothness of the lead layer coverage and the stability of the interface. When the ball milling time is less than 3 hours, the mixing is insufficient, and the metallic phase is difficult to be located in the titanium-lead interface region. When the ball milling time is greater than 6 hours, the powder is overly refined, which is prone to oxidation and agglomeration, which is not conducive to the formation of a stable intermediate metallic phase and lead layer coverage structure. By limiting the ball-to-powder ratio, rotation speed, and ball milling time within the above ranges, and combining them with ultrasonic dispersion treatment, the powders of each phase can be fully mixed, and the raw materials of the metallic material can be effectively located between titanium powder and lead powder. Finally, after sintering, a sufficient interface transition connection is formed, ensuring the shielding performance of the composite lead material against high-energy X-rays and gamma rays.

[0056] In one embodiment, the molding pressure of the cold isostatic pressing process is 1000 MPa to 3000 MPa, and the holding time is 15 min to 40 min.

[0057] For example, the molding pressure of cold isostatic pressing can be 1000 MPa, 1500 MPa, 2000 MPa, 2500 MPa, 3000 MPa, or any value within the above range. The holding time of cold isostatic pressing can be 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, or any value within the above range.

[0058] In the above embodiments, when the molding pressure is less than 1000 MPa, the bonding force between powder particles is insufficient, resulting in low density of the preform. Loose areas of the powder are prone to forming pores or cracks during subsequent sintering, leading to a decrease in radiation shielding performance. When the molding pressure is greater than 3000 MPa, titanium powder particles may undergo excessive plastic deformation, damaging the integrity of the titanium matrix skeleton. Simultaneously, lead powder particles may be excessively compressed, forming localized lead phase accumulation or interface undulations. When the holding time is less than 15 min, pressure transmission is insufficient, resulting in uneven density distribution within the preform. When the holding time is greater than 40 min, the density increase tends to saturate. By limiting the molding pressure and holding time within the above ranges, a dense and uniform preform can be obtained.

[0059] In one embodiment, the sintering temperature of the spark plasma sintering treatment is 950 ℃~1050 ℃, the sintering pressure is 60 MPa~200 MPa, and the holding time is 5 min~20 min.

[0060] For example, the sintering temperature of the spark plasma sintering process can be 950 °C, 980 °C, 1000 °C, 1020 °C, 1050 °C, or any value within the above range. The sintering pressure of the spark plasma sintering process can be 60 MPa, 80 MPa, 100 MPa, 150 MPa, 200 MPa, or any value within the above range. The holding time of the spark plasma sintering process can be 5 min, 8 min, 10 min, 15 min, 20 min, or any value within the above range.

[0061] In the above embodiments, the sintering temperature, sintering pressure, and holding time are controlled within the above range, which can enable the titanium matrix to form a stable skeleton and enable the metal phase to form a transition connection region between the titanium matrix layer and the lead layer, thereby obtaining a composite material with high density and uniform lead layer coverage after sintering, and fully exerting the shielding function against radiation.

[0062] Specifically, sintering temperatures below 950 ℃ result in insufficient formation of sintering necks between titanium particles, inadequate skeleton strength, and high porosity, leading to decreased radiation shielding efficiency. Sintering temperatures above 1050 ℃ cause excessive lead layer flow, resulting in localized deterioration of shielding performance. Sintering pressures below 60 MPa result in insufficient densification driving force, making it difficult to obtain a high-density sintered body and reducing shielding performance. Sintering pressures above 200 MPa cause excessive compression of the titanium skeleton, squeezing the lead layer coverage space and affecting the shielding effect. Holding times below 5 min result in insufficient atomic diffusion and inadequate interfacial bonding, reducing shielding efficiency. Holding times above 20 min exacerbate localized lead layer accumulation, weakening shielding performance. By limiting these parameters within the specified ranges, high and stable radiation shielding efficiency can be achieved while maintaining densification and ensuring uniform lead layer coverage.

[0063] This application provides a high-energy radiation shielding component, comprising the aforementioned composite lead material; and / or, the composite lead material obtained according to the aforementioned preparation method. The composite lead material can be used as a plate-like shielding layer, a sandwich filling layer, an outer shell layer, or a local reinforcing layer in the component.

[0064] In one embodiment, the high-energy radiation protection component includes at least one of a protective wall, an equipment shield, a mobile protective device, a portable protective component, or a nuclear industry equipment enclosure.

[0065] In one embodiment, the protective wall includes an inner support plate, an outer protective plate, and a composite lead material plate sandwiched between the inner support plate and the outer protective plate. The composite lead material plate can be fixed to the wall frame or support structure in the form of spliced ​​panels, modular panels, or staggered overlapping panels. The joints employ staggered or overlapping structures to reduce the risk of radiation leakage through gaps. This protective wall is suitable for fixed shielding spaces such as nuclear medicine imaging rooms, radiotherapy rooms, and industrial flaw detection rooms. The titanium powder particle size, lead powder particle size, and volume percentage of each phase in the composite lead material plate are as described above, ensuring a smooth lead layer coverage and stable interface bonding, thereby improving the radiation shielding efficiency of the wall.

[0066] In one embodiment, the equipment shielding cover includes a frame and a composite lead material layer disposed on the inner or outer side of the frame. The composite lead material layer can be fabricated as a box-type cover, a cylindrical cover, or a curved cover, and connected to the equipment frame by bolts, clips, pressure plates, or welded brackets. It is suitable for radiation sources, irradiation cavities, detector housings, or outer covers for industrial flaw detection equipment. Using a composite lead material layer can improve the radiation shielding efficiency and deformation resistance of the equipment shielding cover while controlling the weight of the shield.

[0067] In one embodiment, the mobile protective device includes a mobile base, a support frame, casters, a handle, and a composite lead shielding plate mounted on the support frame. The composite lead shielding plate can be a single layer or a detachable shielding screen formed by splicing multiple plates, suitable for protective scenarios requiring position adjustment, such as temporary inspection, mobile flaw detection, and radiotherapy auxiliary shielding. Compared to pure lead shielding plates, composite lead shielding plates can reduce the load on the mobile device and improve the structural stability and radiation shielding efficiency of the shielding plate.

[0068] In one embodiment, the portable protective device includes a handheld protective plate, a partial shielding plate, a portable sample protection box liner, or a wearable protective insert, which can improve the radiation shielding efficiency and safety of the portable component.

[0069] For example, composite lead materials can be made into thin sheets, laminates, or small modules, with metal edging or wear-resistant sealing at the edges to reduce the risk of lead layer exposure during handling and reuse. These composite lead materials have high density, uniform lead layer coverage, and stable interfacial bonding, enabling them to provide effective radiation shielding at relatively small thicknesses, thereby improving the radiation shielding efficiency of portable components.

[0070] In one embodiment, the nuclear industry equipment shell includes a pressure-bearing shell, an outer protective shell, or a sandwich shell. Composite lead material is disposed on the outside of the pressure-bearing shell, the inside of the outer protective shell, or between the two to form a sandwich shielding structure. The composite lead material can be fixed by riveting, bolting, slotting, or laminating with a metal shell, and can cooperate with an inner clad lead layer to form a composite shielding structure. This nuclear industry equipment shell is suitable for nuclear industry pipelines, valve boxes, container shells, or testing equipment shells, and can improve the radiation shielding efficiency, interface stability, and long-term structural stability of the equipment shell.

[0071] It should be noted that the thickness, number of layers, plate size and splicing method of the composite lead material layer or composite lead material plate described in the various embodiments of this application are not a limitation on the structural form of the protective component of this application. Those skilled in the art can make adaptive selections and adjustments according to the actual needs of the installation space and usage scenario.

[0072] Examples and Comparative Examples Example 1 Titanium powder, lead powder, and copper powder were weighed in a ratio of 67 vol% titanium matrix, 30 vol% lead phase, and 3 vol% copper metallic phase. Among them, the volume average particle size Dv50 of titanium powder was 30 μm and the oxygen content was 0.12 wt%; the volume average particle size Dv50 of lead powder was 10 μm and the purity was 99.95%; and the volume average particle size Dv50 of copper powder was 2 μm and the purity was 99.9%.

[0073] Titanium, lead, and copper powders, after being treated with supersonic atomization, were dried at 100 °C for 2 h. Anhydrous ethanol (8 wt% of the total raw material mass) was added to the powders, and the mixture was placed in a high-energy ball mill with a ball-to-powder ratio of 8:1, a rotation speed of 600 rpm, and a mixing time of 4 h. The mill was rotated in the reverse direction for 5 min every 30 min, and ultrasonic dispersion at 20 kHz and 500 W was performed. After ball milling, the anhydrous ethanol was removed by drying, yielding a mixed powder. The resulting mixed powder was subjected to cold isostatic pressing at a pressure of 1500 MPa for 20 min to obtain a preform. The preform had a density of 93% of the theoretical density and a porosity of 2.8%. Subsequently, it underwent spark plasma sintering in an argon atmosphere with a purity of 99.99% and a dew point of [missing information]. The sintering temperature was 45 ℃, the sintering pressure was 100 MPa, and the holding time was 10 min. After sintering, the material was annealed at 600 ℃ for 2 h, cooled in the furnace, and then subjected to laser shock peening with a power of 200 W to obtain titanium-based composite lead material.

[0074] The resulting composite lead material has a gamma-ray shielding coefficient of 96%, a tensile strength of 320 MPa, an elongation of 6%, an interfacial bonding strength of 200 MPa, a lead phase dispersion deviation coefficient of 0.15, and an overall density of 9.2 g / cm³.

[0075] Example 2 Titanium powder, lead powder, and nickel powder were weighed in a ratio of 72 vol% titanium matrix, 25 vol% lead phase, and 3 vol% nickel metal phase. Among them, the volume average particle size Dv50 of titanium powder was 40 μm and the oxygen content was 0.14 wt%; the volume average particle size Dv50 of lead powder was 12 μm and the purity was 99.9%; and the volume average particle size Dv50 of nickel powder was 1.5 μm and the purity was 99.9%.

[0076] This embodiment employs a composite structure of cladding and powder metallurgy. The inner layer is a clad lead layer with a thickness of 3 mm, and the outer layer is a titanium-based composite layer. The outer layer material is prepared using powder metallurgy, with a sintering temperature of 950 ℃. The remaining powder mixing, cold isostatic pressing, sintering pressure, holding time, and post-processing steps are the same as in Example 1. The inner clad lead layer is prepared using laser cladding, with a laser power of 300 W, a scanning speed of 1000 mm / s, and a powder feeding rate of 5 g / min, resulting in a composite material for nuclear industry equipment shell protection.

[0077] The resulting composite material has a gamma-ray shielding coefficient of 95%, a tensile strength of 350 MPa, an elongation of 5.5%, an interfacial bonding strength of 180 MPa, a lead phase dispersion deviation coefficient of 0.12, and an overall density of 8.8 g / cm³.

[0078] Example 3 Titanium powder, lead powder, and copper powder were used to form a gradient sintered structure. The surface layer composition was: lead phase 35 vol%, titanium matrix 62 vol%, and copper metal phase 3 vol%; the inner layer composition was: lead phase 20 vol%, titanium matrix 77 vol%, and copper metal phase 3 vol%. The volume average particle size Dv50 of the titanium powder, lead powder, and copper powder was the same as in Example 1.

[0079] First, the surface layer is sintered at a temperature of 1050 ℃; then the inner layer is sintered at a temperature of 950 ℃; the remaining powder mixing, cold isostatic pressing, sintering pressure, holding time and post-treatment steps are the same as in Example 1, to obtain a lightweight protective composite lead material.

[0080] The resulting composite lead material has a gamma-ray shielding coefficient of 95.5%, a tensile strength of 310 MPa, an elongation of 5.8%, an interfacial bonding strength of 170 MPa, a lead phase dispersion deviation coefficient of 0.12, and a density of 8.5 g / cm³.

[0081] Comparative Example 1 100 vol% industrial pure lead was used as the radiation protection material, with a purity of ≥99.9%. Samples of equivalent lead weight were prepared using conventional casting processes.

[0082] The obtained material has a gamma-ray shielding coefficient of 98%, a tensile strength of 14 MPa, a lead phase dispersion deviation coefficient of 0.2, and a density of 11.34 g / cm³.

[0083] Comparative Example 2 Titanium powder and lead powder were weighed at a ratio of 70 vol% titanium matrix and 30 vol% lead phase, without adding copper or nickel powder as the metallic phase. The remaining powder mixing, cold isostatic pressing, spark plasma sintering, and post-treatment steps were the same as in Example 1 to obtain a titanium-lead direct composite material without a metallic phase.

[0084] The obtained material has a gamma-ray shielding coefficient of 85%, a tensile strength of 220 MPa, an interfacial bonding strength of 50 MPa, a lead phase dispersion deviation coefficient of 0.18, and a density of 6.25 g / cm³.

[0085] Table 1. Product parameters of Examples 1-3 and Comparative Examples 1-2 Serial Number Titanium matrix / vol% Lead phase / vol% Metal phase / vol% Metal phase types Example 1 67 30 3 copper Example 2 72 25 3 nickel Example 3 Surface layer 62; Inner layer 77 Surface layer 35; Inner layer 20 Surface layer 3; Inner layer 3 copper Comparative Example 1 / 100 / / Comparative Example 2 70 30 / / Table 2 Performance parameters of Examples 1-3 and Comparative Examples 1-2 Serial Number Shielding coefficient / % Tensile strength / MPa Interfacial bonding strength / MPa Lead phase dispersion deviation coefficient Density (g / cm³) Example 1 96 320 200 0.15 9.2 Example 2 95 350 180 0.12 8.8 Example 3 95.5 310 170 0.12 8.5 Comparative Example 1 98 14 / 0.2 11.34 Comparative Example 2 85 220 50 0.18 6.25 As shown in Tables 1 and 2, Examples 1-3 all used composite materials composed of a titanium matrix, a lead phase, and a metallic phase. The gamma-ray shielding coefficients of the obtained materials were all not less than 95%, indicating that even with a lead phase content lower than that of pure lead materials, high-energy radiation shielding performance could still be maintained. This is because the lead phase, as a high atomic number shielding component, still plays a major role in radiation blocking and attenuation at a given thickness; the titanium matrix, as the main framework, does not replace the shielding function of the lead phase, but rather, while ensuring structural support and lightweighting, allows the lead phase to bond to the titanium matrix in the form of a lead layer through a metallic intermediate phase.

[0086] Combining Example 1 and Comparative Example 1, the gamma-ray shielding coefficient of the pure lead material in Comparative Example 1 is 98%, while that in Example 1 is 96%, both exhibiting high gamma-ray shielding capabilities. However, the tensile strength of Example 1 is 320 MPa, significantly higher than the 14 MPa of Comparative Example 1, while its overall density decreases from 11.34 g / cm³ to 9.2 g / cm³. This demonstrates that Example 1 maintains high gamma-ray shielding performance while improving the material's mechanical strength and reducing its density. This is because the lead phase, as a high atomic number shielding phase, enhances the material's blocking and attenuation capabilities against high-energy X-rays and gamma rays at a given test thickness, thus allowing Example 1 to maintain a 96% gamma-ray shielding coefficient. The titanium matrix, as the main material framework, has a lower density than lead and superior mechanical properties compared to pure lead, enabling it to provide structural support. This increases the tensile strength of the material from 12-18 MPa for pure lead to 320 MPa, while reducing the overall density.

[0087] Combining Example 1 and Comparative Example 2, Comparative Example 2, without the addition of a metallic phase, exhibited an interfacial bonding strength of 50 MPa and a lead phase dispersion deviation coefficient of 0.18. In Example 1, the addition of 3 vol% copper metallic phase increased the interfacial bonding strength to 200 MPa, reduced the lead phase dispersion deviation coefficient to 0.15, and increased the gamma-ray shielding coefficient from 85% to 96%. These results indicate that a metallic phase is beneficial for improving the interfacial bonding between the titanium matrix and the lead phase, and for enhancing the uniformity of lead phase dispersion and the gamma-ray shielding performance of the material.

[0088] As shown in Examples 1 to 3, adjustments to the structure and proportions for different application scenarios result in varying overall performance. Example 1 employs a powder metallurgy structure with a gamma-ray shielding coefficient of 96% and a tensile strength of 320 MPa, making it suitable for medical radiotherapy protective components. Example 2 utilizes a composite structure with an inner clad lead layer and an outer titanium-based composite layer, achieving a gamma-ray shielding coefficient of 95%, a tensile strength of 350 MPa, and an overall density of 8.8 g / cm³, making it suitable for nuclear industry equipment shell protective components. Example 3 employs a gradient sintering structure with a gamma-ray shielding coefficient of 95.5% and an overall density of 8.5 g / cm³, making it suitable for lightweight protective components.

[0089] Parameter testing methods for titanium-based composite lead materials (1) Gamma-ray shielding coefficient As an example, the gamma-ray shielding coefficient is tested using a radiation source and a dose rate meter. During testing, the incident dose rate I0 is measured without a sample, and the dose rate I after the sample is placed is measured. The gamma-ray shielding coefficient η is calculated using the formula η=(I0-I) / I0×100%. Here, I0 is the incident dose rate without a sample, and I is the dose rate after the radiation penetrates the sample. Depending on the application scenario, the test thickness for medical radiotherapy protective samples can be 10 mm, for nuclear industry equipment shell samples it can be 25 mm, and for lightweight protective component samples it can be 6 mm; alternatively, the test thickness can be adjusted according to the target lead equivalent and the component's design thickness.

[0090] (2) Tensile strength and elongation As an example, tensile strength and elongation can be tested in accordance with GB / T 228.1.

[0091] (3) Interfacial bonding strength As an example, the interfacial bonding strength was tested according to GB / T 2790. During the test, a pre-existing peeling start section was prepared between the composite lead material layer and the substrate layer in the sample, and a peeling force was applied in a 180° tensile peeling manner. The average peeling force during the peeling process was recorded, and the interfacial bonding strength was calculated by dividing the average peeling force by the sample width.

[0092] (4) Density As an example, the density was tested using the water displacement method (Archimedes' principle) according to GB / T 3850-2015 "Determination of Density of Dense Sintered Metallic Materials and Hard Alloys". During the test, the mass m1 of the sample in air and the mass m2 in water were weighed separately. The density ρ = m1 / (m2 + m3) / m2. m2)×ρ0, where ρ0 is the density of water at the test temperature.

[0093] (5) Lead phase dispersion deviation coefficient As an example, the lead phase dispersion deviation coefficient is calculated using a combination of scanning electron microscopy backscattered images and grayscale statistics. Specifically, multiple fields of view are selected on the sample cross-section, the lead phase area fraction in each field of view is statistically analyzed, and the ratio of the standard deviation to the mean of the statistical values ​​for each field of view is calculated as the lead phase dispersion deviation coefficient. The smaller the lead phase dispersion deviation coefficient, the more uniform the lead phase dispersion.

[0094] It should be noted that, without conflict, the various embodiments and / or technical features described in this application can be arbitrarily combined with each other, and the resulting technical solutions should also fall within the protection scope of this application.

[0095] It should be understood that the specific examples in the embodiments of this application are only for the purpose of helping those skilled in the art to better understand the embodiments of this application, and are not intended to limit the scope of the embodiments of this application. Those skilled in the art can make various improvements and modifications based on the above embodiments, and all such improvements or modifications fall within the protection scope of this application.

[0096] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A titanium-based composite lead material for high-energy radiation protection, characterized in that, include: At least one titanium-based composite layer, the titanium-based composite layer comprising: a titanium matrix, a lead phase and a metallic phase, wherein the metallic phase is at least partially distributed between the titanium matrix and the lead phase; Based on the total volume of the titanium-based composite layer, the volume percentage of the titanium matrix is ​​60 vol% to 77 vol%, the volume percentage of the lead phase is 20 vol% to 35 vol%, and the volume percentage of the metallic phase is 1 vol% to 8 vol.

2. The titanium-based composite lead material according to claim 1, characterized in that, The metallic phase includes copper and / or nickel.

3. The titanium-based composite lead material according to claim 1 or 2, characterized in that, The volume average particle size Dv50 of the metallic phase satisfies: 1 μm to 3 μm.

4. The titanium-based composite lead material according to claim 1, characterized in that, The titanium matrix material includes titanium powder, and the volume average particle size Dv50 of the titanium powder satisfies: 20 μm to 50 μm.

5. The titanium-based composite lead material according to claim 1, characterized in that, The lead phase material includes lead powder, and the volume average particle size Dv50 of the lead powder satisfies: 5 μm to 15 μm.

6. The titanium-based composite lead material according to claim 5, characterized in that, The volume average particle size Dv50 of the lead powder satisfies: 6 μm to 13 μm.

7. A method for preparing a titanium-based composite lead material for high-energy radiation protection, characterized in that, include: Titanium powder, lead powder, and metallic raw materials are weighed and subjected to high-energy ball milling and ultrasonic dispersion to obtain a mixed powder. The volume percentage of the titanium powder is 60 vol%–77 vol%, the volume percentage of the lead powder is 20 vol%–35 vol%, and the volume percentage of the metallic raw materials is 1 vol%–8 vol%. The mixed powder is subjected to cold isostatic pressing to obtain a preform; the preform is subjected to spark plasma sintering and cooled to obtain the titanium-based composite lead material.

8. The preparation method according to claim 7, characterized in that, The ball-to-material ratio of the high-energy ball milling process is 5:1 to 9:1, the rotation speed is 400 rpm to 800 rpm, and the ball milling time is 3 h to 6 h; and / or, the frequency of the ultrasonic dispersion is 15 kHz to 50 kHz.

9. The preparation method according to claim 7, characterized in that, The forming pressure of the cold isostatic pressing process is 1000 MPa to 3000 MPa, and the holding time is 15 min to 40 min.

10. The preparation method according to any one of claims 7 to 9, characterized in that, The sintering temperature of the spark plasma sintering treatment is 950 ℃~1050 ℃, the sintering pressure is 60 MPa~200 MPa, and the holding time is 5 min~20 min.